Evolution of thermal insulation of plasma-sprayed thermal barrier coating systems with exposure to high temperature. Issue 6 (June 2019) - Boissonnet, G.; Bonnet, G.; Pasquet, A.; Bourhila, N.; Pedraza, F.
Abstract: The thermal insulation potential of plasma-sprayed yttria-stabilized zirconia thermal barrier coatings is generally assessed via the evaluation of the ceramic layer. However, ageing of the complete system leads to microstructural transformations that may also play a role in the heat transport properties. This study thus investigated the microstructure-heat insulation relationships of different TBC systems in their as-deposited state and when aged under various conditions, through the systematic analysis of both microstructure and thermal diffusivity. The latter was measured from room temperature up to 1100 °C using the laser-flash technique, while the porous microstructure was assessed using image analysis. The different coatings exhibited relatively similar thermal diffusivity values that were shown to be mostly influenced by the thin porosities in contrast to larger defects. The thermal insulation of the TBC systems after exposure to high temperature was shown to be stable despite the microstructural variations introduced by cracks, oxidation and chemical degradations.